The Role of Tumour Metabolism in Cisplatin Resistance - Wang, Lude; Zhao, Xiaoya; Fu, Jianfei; Xu, Wenxia; Yuan, Jianlie (Frontiers in Molecular Biosciences, 2021)
Cisplatin is a chemotherapy drug commonly used in cancer treatment. Tumour cells were more sensitive to cisplatin than normal cells. Cisplatin plays an antitumour role by interfering with DNA replication and transcription processes. However, the drug-resistant properties of tumour cells often cause the loss of cisplatin efficacy and the failure of chemotherapy, leading to tumour progression. Because of the large amounts of energy and compounds demanded by tumour cells, metabolic reprogramming plays an important role in the occurrence and development of tumours. The interplay between DNA damage repair and metabolism also has an effect on cisplatin resistance. The molecular mechanisms of changes to glucose metabolism, amino acid metabolism, lipid metabolism and other metabolic pathways affect the cisplatin resistance of tumour cells. We review the mechanism of action of cisplatin, the mechanism of resistance to cisplatin, the role of metabolic remodelling on tumorigenesis and development, and the effects of common metabolic pathways on cisplatin resistance.